Analisis Kinerja Keuangan, Perencanaan Pengendalian Modal dan Piutang Untuk Meningkatkan Stabilitas Keuangan UD Lapar Sehat Jember - Sanjaya, Meliany (Akutansi Bisnis & Manajemen ( ABM ), 2018)
The purpose of this study is to analyze the company's financial performance by analyzing account receivable for working capital efficiency and control of working capital to improve financial stability of the company at UD. Lapar Sehat Jember by analyzing receivables, working capital ratios, and ways of working capital efficiency and management of the company. The results of this study are consideration for company management in determining policies for the circulation of money and the use of working capital and to consider the possible risks that will arise in the company, to determine the level of liquidity, solvency, profitability and stability of the company. The results of the study proves that there is a lot of working capital buried in the company's receivables so that the money circulation in the company experiences delays and makes the company's money turnover unstable, so that the company needs good management in regulating debt to customers and manage well for this can be obtained efficiency and financial stability in the company.